(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
The article intends to contribute to discussions on the foreign policies of Moscow and Ankara focused on their immediate surroundings. Through an analysis of agreements and pacts, it understand how the infrastructure works, ethnic-cultural issues and military aspects are amalgamated in an extremely dynamic scenario since the end of the 20th century. It is in the field of economics that the mainstays of structural problems are found, which has origin in historical rivalries for hegemony in the territory, which is seen here as an expression of power. These disputes are, therefore, very specific forms managed by the diplomacies of countries sensitively guided by the logic of national identities. The result is questions arising whether in the field of international relations there are limits to so many distances and approximations, rivalries and pragmatisms between Turkey and Russia.